2020
DOI: 10.3389/fphys.2020.00932
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Metabolic Responses to Endurance Exercise Under Hot and Hypoxic Conditions

Abstract: Purpose: We explored the effect of heat stress during an acute endurance exercise session in hypoxia on endocrine and metabolic responses. Methods: A total of 12 healthy males cycled at a constant workload (60% of the power output associated with their maximal oxygen uptake under each respective condition) for 60 min in three different environments: exercise under hot and hypoxia (H+H; fraction of inspiratory oxygen or FiO 2 : 14.5%, 32 • C), exercise under hypoxia (HYP; FiO 2 : 14.5%, 23 • C), and exercise un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In the present study, the lower ΔTSI in the HH condition suggested enhanced muscle deoxygenation. This is in line with a study demonstrating that a combined hot and hypoxic environment while cycling at moderate intensity for 60 min tended to produce a lower TSI than thermoneutral normoxic or hypoxic environments (Yatsutani et al, 2020). Hot and hypoxic environments were reported to independently enhance muscle deoxygenation during exercise (Periard et al, 2013;Yamaguchi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the lower ΔTSI in the HH condition suggested enhanced muscle deoxygenation. This is in line with a study demonstrating that a combined hot and hypoxic environment while cycling at moderate intensity for 60 min tended to produce a lower TSI than thermoneutral normoxic or hypoxic environments (Yatsutani et al, 2020). Hot and hypoxic environments were reported to independently enhance muscle deoxygenation during exercise (Periard et al, 2013;Yamaguchi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…A few studies examined this hypothesis, but no consensus was obtained for the effect of combined hot and hypoxic environments on muscle oxygenation during exercise. Yatsutani et al (2020) reported that the tissue saturation index (TSI) during 60-min moderate-intensity cycling tended to be lower in hot hypoxic than thermoneutral hypoxic environments. On the other hand, Yamaguchi et al (2021) failed to observe larger deoxygenation during repeated cycling sprints in a hot hypoxic environment compared with a thermoneutral hypoxic environment.…”
Section: Introductionmentioning
confidence: 99%
“…An inconsistency between TSI and SpO 2 reflects that lowered oxygen saturation was caused in working muscles (local hypoxia), not in blood circulation (systemic hypoxia). Previous studies reported that exercise in normobaric hypoxic conditions elicited lower SpO 2 and TSI compared with normoxia (Willis et al, 2017Yatsutani et al, 2020). Furthermore, the transient reduction in O 2 partial pressure in the muscles during sprint exercise plays a key role in muscular adaptations (Hoppeler et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…They reported mild, transient increases in EPO with training over the 8 weeks. A recent study compared circulating EPO levels in men cycling at 60% of power output at VO 2 max in an environmental chamber under either hot-hypoxic, hypoxic, or normoxic conditions ( 234 ). They reported increases in EPO after the hot-hypoxic and hypoxic conditions, but not under normoxic conditions.…”
Section: Erythropoeitinmentioning
confidence: 99%